6h-11-h=4-37h-2

Simple and best practice solution for 6h-11-h=4-37h-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6h-11-h=4-37h-2 equation:


Simplifying
6h + -11 + -1h = 4 + -37h + -2

Reorder the terms:
-11 + 6h + -1h = 4 + -37h + -2

Combine like terms: 6h + -1h = 5h
-11 + 5h = 4 + -37h + -2

Reorder the terms:
-11 + 5h = 4 + -2 + -37h

Combine like terms: 4 + -2 = 2
-11 + 5h = 2 + -37h

Solving
-11 + 5h = 2 + -37h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '37h' to each side of the equation.
-11 + 5h + 37h = 2 + -37h + 37h

Combine like terms: 5h + 37h = 42h
-11 + 42h = 2 + -37h + 37h

Combine like terms: -37h + 37h = 0
-11 + 42h = 2 + 0
-11 + 42h = 2

Add '11' to each side of the equation.
-11 + 11 + 42h = 2 + 11

Combine like terms: -11 + 11 = 0
0 + 42h = 2 + 11
42h = 2 + 11

Combine like terms: 2 + 11 = 13
42h = 13

Divide each side by '42'.
h = 0.3095238095

Simplifying
h = 0.3095238095

See similar equations:

| 6h-11-h=4-37h-3 | | 5x-8=4x+3(x+1) | | 4-3x=274 | | A/36=3/8 | | 5.6+x=6.3 | | 5d+10+4=13.50 | | 0.6x-1.2=8.4 | | 0=12x^2+8-15 | | 5.6+x= | | Log(9)(x+2)=log(9)(3x+5) | | Y=3x^2-2-6x | | n+240=300 | | 4-3x=-274 | | x=12+8 | | -9-6=-4 | | 14+2/3t=8 | | g-3.5=1.25 | | 0=-3x^2+6x-3 | | y+1.5y-0.2=4.2y-18.9 | | x=x^2+84r+1728 | | 40=5(5-x) | | 2.5+r=4 | | y=-3x^2+6x-3 | | Y=3x^2-2x-6x | | x=28+12 | | t-31=30 | | 20x-(7x-5)=96 | | f(x)=(x+5)2-8 | | F(x)=2x-x+1 | | f-12=10 | | d+32=70 | | f(x)=-x^2+10x+17 |

Equations solver categories